Soil chemical properties and water quality at Miahuatlán de Porfirio Díaz and Ejutla de Crespo, Oaxaca, Mexico - Zárate-Martinez, William; Felipe-Victoriano, Moisés; Martínez-Silva, Fernando Edgar; Móreno-León, Karina; Arispe-Vázquez, José Luis; Díaz-Nájera, José Francisco (Ecosistemas y Recursos Agropecuarios, 2024)
The research was performed in the cycle 2020, with the objective of determining the chemical characteristics of the soil and water quality in the municipalities of Miahuatlán de Porfirio Díaz and Ejutla de Crespo, Oaxaca, Mexico. The soil and water were sampled, the content of cations, anions and water quality variables were determined. High concentrations of Ca and Mg were recorded in the soil with average values of up to 19.20 and 19.42 mEq L-1 respectively. High concentrations of Ca2+, Mg2+ and HCO3- were recorded in the water with average values of up to 4.79, 4.32 and 7.97 mEq L-1 respectively. According to the variables SP, RAS, IS and CSR, the water is classified as suitable for irrigation. It is concluded that the use of acids is necessary to lower the pH of the water and neutralize the carbonates.
Keywords: nutrient solution; cations; anions; carbonates; bicarbonates